2008
DOI: 10.1890/07-1429.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Net Effects of Pesticides on Amphibian Trematode Infections

Abstract: Anthropogenic factors can have simultaneous positive and negative effects on parasite transmission, and thus it is important to quantify their net effects on disease risk. Net effects will be a product of changes in the survival and traits (e.g., susceptibility, infectivity) of both hosts and parasites. In separate laboratory experiments, we exposed cercariae of the trematode Echinostoma trivolvis, and its first and second intermediate hosts, snails (Planorbella trivolvis) and green frog tadpoles (Rana clamita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
200
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(207 citation statements)
references
References 77 publications
5
200
1
1
Order By: Relevance
“…Further, this study provides the first evidence in a vertebrate species that evolutionary responses to pesticides influence susceptibility to parasites. Pesticide‐mediated effects on disease outcomes are commonly documented in the literature, yet the results are often variable with pesticides increasing host tolerance to parasite infection in some cases (Coors, Decaestecker, Jansen, & De Meester, 2008; Kiesecker, 2002; Rohr, Raffel, et al., 2008) but not in others (Griggs & Belden, 2008; Marcogliese et al., 2009; Schotthoefer et al., 2011). We demonstrate that the mechanism underlying the evolution of pesticide tolerance may be critical for assessing susceptibility to parasites.…”
Section: Discussionmentioning
confidence: 85%
“…Further, this study provides the first evidence in a vertebrate species that evolutionary responses to pesticides influence susceptibility to parasites. Pesticide‐mediated effects on disease outcomes are commonly documented in the literature, yet the results are often variable with pesticides increasing host tolerance to parasite infection in some cases (Coors, Decaestecker, Jansen, & De Meester, 2008; Kiesecker, 2002; Rohr, Raffel, et al., 2008) but not in others (Griggs & Belden, 2008; Marcogliese et al., 2009; Schotthoefer et al., 2011). We demonstrate that the mechanism underlying the evolution of pesticide tolerance may be critical for assessing susceptibility to parasites.…”
Section: Discussionmentioning
confidence: 85%
“…We suspect that, to thoroughly understand climatic effects on Bd-related declines, investigators will need to explicitly test how climate affects interactions between Bd and amphibian hosts, as well as consider other factors altering host-parasite dynamics or host fitness directly (39,(42)(43)(44). Additionally, the influence of climate on amphibians will almost certainly depend on the local scales at which organisms experience climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Coors and De Meester (2008) found that exposure to the insecticide carbaryl had a synergistic effect on Daphnia magna by increasing susceptibility to the parasite Pasteuria ramosa. Similarly, in amphibians, Rohr et al (2008) found that green frog tadpoles exposed to the herbicide atrazine had significantly higher levels of encysted trematodes (Echinostoma trivolvis). Further, Kiesecker (2002) linked pesticide exposure to increased infection and pathology (i.e., limb malformations) in amphibians exposed to the trematode Ribeiroia ondatrae.…”
Section: Introductionmentioning
confidence: 91%
“…Mounting evidence suggests that pesticides can influence disease outcome directly (e.g., mortality) and indirectly (e.g., immune suppression; Carey et al 1999;Kiesecker, 2002;Christin et al 2004;Rohr et al 2008). For instance, Coors and De Meester (2008) found that exposure to the insecticide carbaryl had a synergistic effect on Daphnia magna by increasing susceptibility to the parasite Pasteuria ramosa.…”
Section: Introductionmentioning
confidence: 99%